Modeling Downward Groundwater Leakage Rate to Evaluate the Relative Probability of Sinkhole Development at an Under-Construction Expressway and Its Vicinity - Xiao, Han; Li, Haiming (Frontiers in Earth Science, 2020)
Sinkhole developments have been recognized as one of the primary geo-hazards which pose a great threat to infrastructure such as buildings, roads, bridges, and pipelines, resulting in huge financial losses to society. Previous studies indicated that sinkhole spatial density increases linearly with downward groundwater leakage rate (DGLR) (inter-aquifer flowrate from the unconfined to the confined aquifer through the aquitard between them) and spatial variation of annual-average DGLR is a useful indicator of relative probability of sinkhole development. In this study, a groundwater flow model using the MODFLOW computer code was developed and calibrated to simulate spatial variation of annual-average DGLR for evaluation of relative probability of sinkhole development at a constructing expressway and its vicinities. Results indicated that the expressway under construction has relatively high probability of sinkhole development in the designed range of the pavement structures, and engineering actions should be taken in advance to minimize potential sinkhole hazards.